EMC.
" ... articles on all aspects of skin and venereal diseases, [including] microbiology, sexually transmitted diseases, immunology, allergy and skin toxicology, skin physiology and biochemistry ..."--Publisher information page (Elsevier, viewed July 5, 2004).